T1 mapping, T2 mapping and MR elastography of the liver for detection and staging of liver fibrosis. - Hoffman, David H.; Ayoola, Abimbola; Nickel, Dominik; Han, Fei; Chandarana, Hersh; Shanbhogue, Krishna Prasad (Abdominal Radiology, 2020)
Purpose: To compare liver stiffness measurements obtained from MR elastography with liver T1 relaxation times obtained from T1 mapping and T2 relaxation times obtained from T2 mapping for detection and staging of liver fibrosis. Materials and methods: 223 patients with known or suspected liver disease underwent MRI of the liver with T1 mapping (Look-Locker sequence) and 2D SE-EPI MR elastography (MRE) sequences. 139 of these patients also underwent T2 mapping with radial T2 TSE sequence. Two readers (R1 & R2) measured liver stiffness, T1 relaxation times and T2 relaxation times. T1 and T2 times were correlated with stiffness measurements. ROC analysis was used to compare the performance of both techniques in discriminating fibrosis stage in 23 patients who underwent liver biopsy. Results: For each reader there was significant moderate positive correlation between liver MRE and liver T1 mapping (r = 0.49 and 0.36). There was significant moderate positive correlation between liver T2 mapping and each of MRE and T1 mapping for one of the readers (r = 0.40 and 0.27). AUC for differentiating early (F0–F2) from advanced (F3–F4) fibrosis in biopsied patients was 0.975 (R1) and 0.925 (R2) for MRE, 0.671 (R1) and 0.642 (R2) for T1 mapping and 0.671 (R1) and 0.743 (R2) for T2 mapping. Inter-reader agreement was good for MRE (ICC = 0.84) substantial for T1 mapping (0.94) and T2 mapping (0.96). Conclusions: Liver T1 and T2 mapping showed moderate positive correlation with MR elastography. Accuracy of MRE is however superior to T1 and T2 mapping in the subset of patients who underwent liver biopsy. Accuracy of combination of MRE and T1 mapping/T2 mapping was not superior to MRE alone.